TINJAUAN YURIDIS TENTANG WANPRESTASI PERJANJIAN ANTARA PEKERJA KONTRAK (PKWT) TERHADAP PERUSAHAAN DI PT. TENAGO TRIMINDO (BERDASARKAN UNDANG – UNDANG NO 13 TAHUN 2003 TENTANG KETENAGAKERJAAN) - Ervaneli, Ervaneli; Febrianti, Lidia; S, Thamrin (Jurnal Kajian Ilmu Hukum, 2022)
At a company called pt. Tenago trimindo engaged in the farmers' forest industry, they made an agreement with the people who became workers/ laborers. The employment contract is made as an anticipation that each party will have the opportunity to default in the future. Both from the pt. Tenago trimindo or it could be from the employees. After some time has passed, a work agreement has been agreed between the company and the workers, the facts on the ground explain that the people who work have deviated from the agreed work contract. The fact that the author got from various information there are several contract workers/labor contract treason, both work contracts and collective labor contracts, the violation committed by contract workers/laborers is to run away from the company before the work contract expires, while in the agreement made by pt. Tenago trimindo which has been agreed upon by contract workers/laborers must complete the term of their work contract properly. As for in this study, there are main problems that will be discussed, namely, the factors occurring default agreements between contract workers against pt. Tenago trimindo and the second is legal remedies that can be carried out by the company if the contract workers do not fulfill the contents of the contract work agreement. And the purpose of this study is the same as the formulation of the main problem, namely to find out the results of the formulation of the problem made by the researcher. This legal research belongs to the type of survey research (observational research). This type of research method is intended to solve problems that exist at the present time by collecting data and compiling or clarifying it, then analyzing and seeing a legal reality in society to then obtain a result The results of the research that the authors obtained are factors that influence the occurrence of defaults carried out by contract workers against the company pt. Tenago trimindo are: irregular working hours factors, late payment of basic salary factors, work pressure factors, non-fulfillment of workers' rights, inappropriate job descriptions. The legal remedies that can be taken by the company if the contract workers do not fulfill the contents of the contract work agreement are settlements by the disputing parties so that results that benefit both parties can be obtained. Such a bipartite settlement can be carried out through deliberation and consensus by the parties without being interfered with by any party. However, if the settlement of the non-litigation path cannot be reached, then the litigation route is taken, namely the industrial relations court, hereinafter referred to as PHI.